2011
DOI: 10.1007/s00264-011-1206-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of anterior cruciate ligament reconstruction: a comparison with non-operative treatment with a follow-up of 17–20 years

Abstract: We can conclude that 94% of patients who underwent ACL reconstruction had stable knees after 15-20 years and there was a significantly lower percentage of osteoarthritis in comparison to conservatively treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(112 citation statements)
references
References 19 publications
4
106
0
2
Order By: Relevance
“…Milhelic et al published a report comparing operative versus conservative treatment and reported significant differences in OA rate between groups, with a significantly higher rate of OA with increased laxity. Furthermore, they reported the highest OA rate with concomitant menisectomy [18]. In this report, radiographic evaluation of OA revealed no signs of degenerative changes in 86.7% of patients on pretrauma assessment.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Milhelic et al published a report comparing operative versus conservative treatment and reported significant differences in OA rate between groups, with a significantly higher rate of OA with increased laxity. Furthermore, they reported the highest OA rate with concomitant menisectomy [18]. In this report, radiographic evaluation of OA revealed no signs of degenerative changes in 86.7% of patients on pretrauma assessment.…”
Section: Discussionmentioning
confidence: 70%
“…Further clinical evaluation criteria consisted of Tegener and Lysholm score [16,26]. Patients who scored >92 points were considered to have excellent results; scores between 91 and 76 points were good; scores <76 points were fair/poor according to the Lysholm score [18]. Clinical evaluation using both IKDC and Lysholm scores was performed 24 months after surgery and at the ten to 15-year followup.…”
Section: Assessmentsmentioning
confidence: 99%
“…Mihelic et al [31] retrospectively studied outcome of 33 operated BTPB grafts with 17 to 20 year follow-up with 83% of patients having stable knees with normal or near normal IKDC grades and an IKDC score of 83.15, they do not however report re-rupture rates. Gerhard et al [32] report 16 year mean follow-up of 63 patients after BTPB ACL reconstruction with 84% returning to previous sporting levels with 78% normal or near normal IKDC grades and a KOOS score of 84.…”
Section: Graft Choicementioning
confidence: 99%
“…The KANON study (the Knee, Anterior cruciate ligament, NON-surgical versus surgical treatment) [89] found no difference in muscle power and functional tests between strength training with surgical intervention when compared to conservative management strategies at 2-5 years of followup. However, the development of osteoarthritis in the knee was reported to be increased in non-operative ACL-injured patient [90] compared a delayed progression in patients with ACLR after 15-20 years of followup [91].…”
Section: Decision Making Prior To Surgerymentioning
confidence: 99%